Analysis of Laston Ac-Wc Mixed With Reclaimed Asphalt Pavement (RAP) and Adding Styrofoam Based on Marshall Parameters - Falderika Falderika; Bahtiar Bahtiar (Eduvest - Journal of Universal Studies, 2022)
One option that has the potential to be applied to road roughness is the reuse of Reclaimed Asphalt Pavement (RAP) material. RAP material can be reused by adding new asphalt and aggregate in accordance with the composition of the mixture so that it is expected to obtain the quality as planned. One of the efforts made to improve the quality of the RAP asphalt mixture is to use modified asphalt with additional material in the form of styrofoam. The use of styrofoam in asphalt is expected to improve the technical properties of a mixture. This research was conducted with variations in asphalt content of 5%, 5.5%, 6%, 6.5%, and 7%. bitumen content obtained from extraction is 6.28%, and the use of RAP is 30%. Next, make specimens for the standard marshall test at variations in Styrofoam levels of 0%, 6.5%, 6.75% and 7% on each KAA and the KAO value is 6.75% of the weight of the test object. The results of the Marshall test showed the optimum stability value for adding that the effective percentage of Styrofoam was found in a mixture of 7% Styrofoam, which was 4181 kg with an increase of 4,700 from a mixture of laston without Styrofoam addition. The flow value is 2.76 mm, while the Marshall Quotient (MQ) value has increased compared to without the use of Styrofoam with a value of 1.513. From the results of mixed analysis using RAP with the addition of optimum Styrofoam, it can improve the performance of the laston AC-WC mixture.